Desenvolvimento econômico em cidades da fronteira amazônica: ações, escalas e recursos para Oiapoque-AP - Gutemberg de Vilhena Silva (Confins)
This essay has a twofold purpose: to characterize and simultaneously assess the potential for economic development in the municipality of Oiapoque (state of Amapá), located on the northern border of Brazil. Initially, this work evaluates general information with statistical data from the last census of Instituto Brasileiro de Geografia e Estatística (IBGE) and Portal Transparência from the Brazilian Federal Government. Next, an assessment of the factors that directly influence the economic development from Oiapoque is made. The research methodology was divided into three steps: 1) bibliographicand documentary research, 2) field work, on which most part of the presented data on the second section were collected, and 3) laboratory analysis of the results from the last two steps. Generally, the paper concludes that Oiapoque is an urbanized city with a significant population increase over the past ten years without accompanying improvement in quality of life for residents. In addition, it was found that its geographical position border, the land structure and socio-economic, public policy and lack of infrastructure are keys to understanding and / or path to economic development.